STUDY OF INSULIN RESISTANCE IN PREGNANCY WITH IMPAIRED GLUCOSE TOLERANCE - B.JYOTHIRMAYI,; M.VASANTHA, (International Journal of Pharma and Bio Sciences, 2016)
Pregnancy is a diabetogenic state which alters carbohydrate metabolism, influences insulin production and its regulation resulting in insulin resistance state. Decreased insulin sensitivity and associated risk factors like obesity can lead to development of diabetes over a period of time if not monitored regularly. Two groups of women were studied: pregnant women with normal glucose tolerance (n =30) as control and pregnant women with impaired glucose tolerance (n=30) as subjects Insulin levels were significantly high in subjects compared to controls. (14.55±5.5 7.25±5.0 P< 0.001).Insulin resistance was calculated using HOMAIR (2.9±1.7 1.45±0.0.87).Our study suggests that pregnant women with impaired glucose tolerance display a state of insulin resistance.